Self-Assembly of PPC Molecules on Carbon Nanotubes: Insights from Coarse-Grained Molecular Dynamics Simulations - Fan Maozhen (BIO Web of Conferences)
Carbon nanotubes (CNTs) have emerged as promising nanocarriers in drug delivery and biomedical imaging due to their unique physicochemical properties. Understanding the interactions between lipids and CNTs, as well as the resulting adsorption morphologies, is crucial for optimizing their applications. In this study, we employed coarse-grained molecular dynamics simulations to investigate the adsorption behavior of palmitoylphosphatidylcholine (PPC) molecules on CNTs suspended above and below a lipid-water monolayer. By analyzing CNTs with a diameter of 4 nm, we explored the self-assembly patterns and mechanisms underlying the formation of distinct adsorption morphologies. Our results reveal that the inner surface of CNTs exhibits a higher affinity for PPC adsorption, forming ring-like structures, while the outer surface displays irregular patterns. Additionally, the tails of PPC molecules adsorbed on the outer surface tend to align parallel to the CNT axis, minimizing bending energy. The probability distribution of angles between PPC tails and the CNT axis on the outer surface was found to be similar to that in the solution. These findings provide new insights into the lipid-CNT interactions and the factors governing their self-assembly, offering valuable guidance for the design of CNT-based nanocarriers.